A season in the wilderness : ecoativismo, identidade e topofilia em “Desert Solitaire”, de Edward Abbey - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This study is an analysis of approaches from the point of view of both ecocriticism and space theories on the autobiographical report Desert Solitaire: A Season in the Wilderness (1968), by Edward Abbey (1927-1989), an US author, born in Indiana. The study aims to focus on the relationship between man and nature based on the author's own experiences during a period of time when he was closer to wilderness, as a ranger at the Arches National Monument, between 1956 and 1957. Although the book had been written based on the experiences from the mentioned period the author has always been in contact with the nature of the American Southwest and West since his early years. The observation about Edward Abbey's coexistence with nature, from an early age, allowed some reflections about his relationship with wilderness perceived by him as positive. It was also possible to understand the author's ecoactivist behavior in Desert Solitaire and in the whole of his work (not studied in the present work) revealed from the research carried out for the elaboration of this text. The author's reflections concerning his experiences in the desert aroused the urgent protagonism of man, facing the challenge of promoting progress, understanding that economic development must advance concomitantly to a project of factual environmental preservation. Abbey's writing identifies a potential defense of nature and philosophical reflections on the need to preserve desert life, as also the life of the planet. Desert Solitaire “immortalized” the author's activism and his voice that echoed in the desert in favor of human and non-human life. In this book, there is an inventory of the spatial elements of the desert, poetic descriptions of the space, suggestions for ecotourism practices, above all, the author criticizes man's destructive actions in relation to nature, through an intense literaty discourse. This book contributes to a current preservation debate, which is a worldwide concern. Abbey’s book has also a high aesthetical value due to the artistic quality of his experience repport, what makes possible, including, a literary reading.
Keywords: Ecocrítica; Ecoativismo; Deserto; Preservação; Literatura; Ecocritical; Ecoactivism; Wilderness preservation; Literature; LINGUISTICA, LETRAS E ARTES